Cost benefit analysis of agroecological transition: A case of mango value chain in Kenya - Ndiwa, Aurillia M.; Onyango, Kevin; Bolo, Peter; Wanyama, Rosina; Chege, Christine G. K (2024)
Current food system is not sustainable evidenced by persistent poverty, malnutrition, and environmental degradation. Agroecology (AE) has been identified as an approach that could help in addressing this challenge and supporting food system transformation. There is inadequate evidence on the cost and benefits associated with agroecological interventions in the food system.